The current approach to soil remediation: A review of physicochemical and biological technologies, and the potential of their strategic combination. Issue 2 (April 2022) - Aparicio, Juan Daniel; Raimondo, Enzo Emanuel; Saez, Juliana María; Costa-Gutierrez, Stefanie Bernardette; Álvarez, Analía; Benimeli, Claudia Susana; Polti, Marta Alejandra
Abstract: In the last decades, the growing industrial activities, rapid urbanization, highest consumption rates, and non-safe human practices have greatly increased soil pollution with contaminants, including pesticides, heavy metals, hydrocarbons, chlorophenols, and polychlorinated biphenyls. Different physicochemical and biological remediation technologies have emerged to deal with this problem and allow a progressive solution. Physicochemical treatments present high speed and efficiency, but most of them are expensive, laborious, and destruct the soil functionality. Biological treatments, in contrast, present eco-friendly features and a greater social acceptance, but they require longer periods to remove pollutants from soils. However, all the restrictions related to the type and concentration of pollutants, the edaphic characteristics, accessibility to the affected region, and the cost of the process, among others, can be offset through a combination of treatments. In particular, successful cases combining physicochemical and biological technologies are discussed, overcoming their limitations and synergistically improving the efficiency in the degradation of pollutants. Some of these technologies have been tested on a pilot-scale, and even on a field-scale, with different performances. Therefore, this review intends to concentrate and discuss the existing information to facilitate decision-making on which is the most appropriate technology for each particular situation, optimizing economic and human resources and working times. However, more studies and practical applications are required as the combination of strategies could represent the future of the restoration of contaminated environments. Graphical Abstract: ga1 Highlights: Physicochemical and biological technologies are effective for soil remediation. Physicochemical treatments are fast and efficient but expensive and laborious. Biological remediation treatments are eco-friendly but require longer periods. Combining technologies overcome their limitations and improve the efficiency. Bases, pros/cons, prospects, and uses of soil remediation techniques are discussed.